2022
DOI: 10.1108/aaouj-09-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Learner characteristics attributable to completion and duration of completion in engineering and science degree programmes of OUSL

Abstract: PurposeThe purpose of this study is to identify the learner characteristics attributable to the likelihood and the duration of programme completion in the Bachelor of Science (BSc) and Bachelor of Technology Honours in Engineering (BTech) degree programmes of the Open University of Sri Lanka (OUSL).Design/methodology/approachData were gathered from the re-registrants for the degree programmes in the academic year 2020/2021, using a questionnaire developed as a Google form. The sample consisted of 301 and 516 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The results revealed that distance learning had a significant effect on increasing students' sense of value (self-esteem) by increasing their confidence and feelings of independence with the educational process. This was reflected in an increased feeling of satisfaction with their academic activities and increased happiness with their academic achievements [ 55 ]. The results also showed that distance learning had a positive impact on students' social relationships, and they became more involved and present because the content of the material felt fun, exciting, and adapted to the individual student's preferred learning style [ 2 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that distance learning had a significant effect on increasing students' sense of value (self-esteem) by increasing their confidence and feelings of independence with the educational process. This was reflected in an increased feeling of satisfaction with their academic activities and increased happiness with their academic achievements [ 55 ]. The results also showed that distance learning had a positive impact on students' social relationships, and they became more involved and present because the content of the material felt fun, exciting, and adapted to the individual student's preferred learning style [ 2 , 56 ].…”
Section: Discussionmentioning
confidence: 99%